1999
DOI: 10.1093/humrep/14.1.136
|View full text |Cite
|
Sign up to set email alerts
|

Reversion of the differentiated phenotype and maturation block in Sertoli cells in pathological human testis

Abstract: To study the relationship between abnormal Sertoli cell differentiation and spermatogenic impairment, we examined the expression of Sertoli cell markers normally lost at puberty, cytokeratin 18 (CK18), anti-Müllerian hormone (AMH) and M2A antigen, in three children (aged 1-2 years), 50 adults (aged 19-45 years) with obstructive or non-obstructive azoospermia or oligozoospermia, and six patients (aged 1-18 years) with 5 alpha-reductase deficiency. There was CK18 and/or AMH expression, but never M2A antigen expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
1
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 33 publications
8
64
1
2
Order By: Relevance
“…AMH causes the Müllerian duct to degenerate in XY embryos and promotes testicle differentiation. It has been reported that Amh and Krt18 are expressed in immature testes, but are absent in adult testes [13,67,68]. Unexpectedly, we detected both of them in adult male mice.…”
Section: Differential Expression Of Biomarkers In Testisspecific Cellssupporting
confidence: 53%
“…AMH causes the Müllerian duct to degenerate in XY embryos and promotes testicle differentiation. It has been reported that Amh and Krt18 are expressed in immature testes, but are absent in adult testes [13,67,68]. Unexpectedly, we detected both of them in adult male mice.…”
Section: Differential Expression Of Biomarkers In Testisspecific Cellssupporting
confidence: 53%
“…21 of the 51 cases showed seminiferous tubules with Sertoli cells expressing cytokeratin 18. These tubules show close similarities with those indicated within former studies [5,6]. In accordance with these studies we additionally observed cytokeratin 18 expression in unfolded tubules with spermatogenic arrest at the level of spermatogonia or only few remaining Sertoli cells and partially sclerohyalinized tubular membranes.…”
Section: Discussionsupporting
confidence: 91%
“…One of these proteins is cytokeratin 18, an intermediate filament protein, which is consistently expressed in immature Sertoli cells of (normal) prepubertal seminiferous tubules, but is completely absent in normal, mature seminiferous tubules [1]. Cytokeratin 18 immunoactivity was found in Sertoli cells of tubules showing spermatogenic arrest at the level of spermatogonia and in some Sertoli cell only tubules with immature Sertoli cells which are frequently observed within so-called mixed atrophy biopsies [1][2][3][4][5][6][7]. Therefore, the immunohistochemical detection of cytokeratin 18 in Sertoli cells is supposed to be a sensitive marker for immature Sertoli cells.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, cytokeratin 18 is a robust marker of immature Sertoli cells and in adult testes it has been used to identify seminiferous tubules in which the Sertoli cells have not matured (Stosiek et al, 1990;Steger et al, 1996Steger et al, , 1999Maymon et al, 2000), though this has also been indicated as reflecting de-differentiation of mature Sertoli cells (Kliesch et al, 1998;Steger et al, 1999).…”
Section: Cytokeratin 18mentioning
confidence: 99%
“…M2A is expressed only by immature and not mature Sertoli cells in humans (Baumal et al, 1989), and its expression may persist in patients in whom disorders of spermatogenesis are present (Steger et al,1999;Blagosklonova et al, 2002).…”
Section: M2a Antigenmentioning
confidence: 99%